The influence of firn layer material properties on surface crevasse propagation in glaciers and ice shelves - T. Clayton; R. Duddu; R. Duddu; T. Hageman; E. Martínez-Pañeda; E. Martínez-Pañeda (The Cryosphere)
Linear elastic fracture mechanics (LEFM) models have been used to estimate crevasse depths in glaciers and to represent iceberg calving in ice sheet models. However, existing LEFM models assume glacier ice to be homogeneous and utilize the mechanical properties of fully consolidated ice. Using depth-invariant properties is not realistic as the process of compaction from unconsolidated snow to firn to glacial ice is dependent on several environmental factors, typically leading to a lower density and Young's modulus in upper surface strata. New analytical solutions for longitudinal-stress profiles are derived using depth-varying properties based on borehole data from the Ronne Ice Shelf and are used in an LEFM model to determine the maximum penetration depths of an isolated crevasse in grounded glaciers and floating ice shelves. These maximum crevasse depths are compared to those obtained for homogeneous glacial ice, showing the importance of including the effect of the upper unconsolidated firn layers on crevasse propagation. The largest reductions in the penetration depth ratio were observed for shallow grounded glaciers, with variations in Young's modulus being more influential than firn density (maximum differences in crevasse depth of 46 % and 20 %, respectively), whereas firn density changes resulted in an increase in penetration depth for thinner floating ice shelves (95 %–188 % difference in crevasse depth between constant and depth-varying properties). Thus, our study shows that the firn layer can increase the vulnerability of ice shelves to fracture and calving, highlighting the importance of considering depth-dependent firn layer material properties in LEFM models for estimating crevasse penetration depths and predicting rift propagation.